2012
DOI: 10.5888/pcd9.110155
|View full text |Cite
|
Sign up to set email alerts
|

Replicating the EnhanceFitness Physical Activity Program in Hawai<i's Multicultural Population, 2007-2010

Abstract: BackgroundDespite evidence of the benefits of regular physical activity, many older adults are not physically active. Health professionals are challenged to replicate evidence-based programs to address low levels of physical activity among members of their communities.Community ContextEnhanceFitness is an evidence-based group exercise program developed in Seattle to increase the strength, flexibility, and balance of older adults. Hawai`i's Healthy Aging Partnership supported the rural island of Kaua`i to selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 8 publications
(15 reference statements)
2
20
0
Order By: Relevance
“…Overall, EF has reached a racially diverse population of older adults, including African Americans and Asian/ Pacific Islanders. 11,12 Participants are predominately female and aged 470 years. 5,6,[11][12][13] EF participants, on average, reported a range of 0.5-1.48 chronic conditions as indicated by the Charlson Comorbidity Index.…”
Section: Reachmentioning
confidence: 99%
“…Overall, EF has reached a racially diverse population of older adults, including African Americans and Asian/ Pacific Islanders. 11,12 Participants are predominately female and aged 470 years. 5,6,[11][12][13] EF participants, on average, reported a range of 0.5-1.48 chronic conditions as indicated by the Charlson Comorbidity Index.…”
Section: Reachmentioning
confidence: 99%
“…A university partner could help identify cultural discrepancies to ensure a Westernbased program could be adapted to Chinese culture. The training manual would need to be translated and culturally sensitive marketing materials would need to be developed; the name EnhanceFitness might need to be changed to better resonate with locals (Tomioka, Sugihara, & Braun, 2012); and music played during the class would likely need to be adapted. The academic partner could also provide oversight to the program to assure program fidelity.…”
Section: Partnershipsmentioning
confidence: 99%
“…Intervention studies have documented the efficacy of EF and have shown that EF improves performance on fitness assessments, perceived physical functioning, social functioning, mental health, and decreases bodily pain [1518]. Limited evidence exists demonstrating that EF can be translated to community-based settings and still achieve improvements in fitness and wellbeing [19]. Therefore, we investigated the ability of HARC to implement and sustain the EF program in South Florida over a three-year period.…”
Section: Introductionmentioning
confidence: 99%